2004
DOI: 10.1021/ol0362921
|View full text |Cite
|
Sign up to set email alerts
|

Anion Radicals of Di-trans-[12]annulene and Heptalene in a One-Pot Synthesis from a Common Fire Retardant

Abstract: [reaction: see text] Low temperature (-100 degrees C) dehydrohalogenation of 1,2,5,6,9,10-hexabromocyclododecane (a common fire retardant) with potassium tert-butoxide in THF followed by one-electron reduction yields the anion radical of the di-trans form of [12]annulene. This system yields a well-resolved EPR signal that reveals that most of the spin density resides on one side (the planar side) of the anion radical. Five of the carbons in this [12]annulene system are twisted from the plane of the remaining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…Annulenes have attracted much attention since the first report on [8]annulene in 1911 . Many efforts have been devoted to probing the (anti)aromaticity of [4 n ]annulenes by using NMR spectroscopy and computational methods. The addition of π-electrons to the [4 n ]annulenes that are antiaromatic in the Hückel sense has been carried out to alter their aromaticity and magnetic properties. Among the [4 n ]annulenes, studies on [12]annulenes and hetero[12]annulenes are very limited due to their decreased thermal stability. , Stevenson reported that [12]annulenes show diamagnetic properties 10a…”
mentioning
confidence: 99%
“…Annulenes have attracted much attention since the first report on [8]annulene in 1911 . Many efforts have been devoted to probing the (anti)aromaticity of [4 n ]annulenes by using NMR spectroscopy and computational methods. The addition of π-electrons to the [4 n ]annulenes that are antiaromatic in the Hückel sense has been carried out to alter their aromaticity and magnetic properties. Among the [4 n ]annulenes, studies on [12]annulenes and hetero[12]annulenes are very limited due to their decreased thermal stability. , Stevenson reported that [12]annulenes show diamagnetic properties 10a…”
mentioning
confidence: 99%
“…Tri-trans isomer 1a (Scheme ) was reportedly synthesized over 30 years ago by Oth and co-workers, although one [4n]annulene review casts doubt on the matter, whereas another review devotes only a few sentences to [12]annulene, stating that “there has been very little recent work” on it 1b. Indeed, at the time of both reviews, the most recent experimental work was the report of Stevenson and co-workers, who repeated Oth's synthesis of 1a to make the corresponding radical anion. ,
1
…”
mentioning
confidence: 99%
“…The reduction of the di-trans isomer (4b) with K was recently reported [76]. Its radical anion has a different EPR spectrum (13.5 G) from that of the tri-trans isomer.…”
Section: [12]annulenementioning
confidence: 90%
“…C 78 and C 84 were reduced as a mixture of isomers, and in some of the measurements the different isomers could be distinguished. The EPR measurements by Pénicaud [152] showed that the g values of all of the monoanions were higher than that of C 60 À (2.0023, 2.0018 and 2.0008 for C 76 À , C 78 À , C 84 À , respectively, in benzonitrile). In tetrachloroethane the two isomers of C 78 À could be distinguished by their different EPR characteristics [152].…”
Section: Reduced Higher Fullerenesmentioning
confidence: 97%